Expression of Zinc Transporter Genes in Rice as Influenced by Zinc-Solubilizing Enterobacter cloacae Strain ZSB14 - Krithika, Selvaraj; Balachandar, Dananjeyan (Frontiers in Plant Science, 2016)
Zinc (Zn) deficiency in major food crops has been considered as an important factor affecting the crop production and subsequently the human health. Rice (Oryza sativa) is sensitive to Zn deficiency and thereby causes malnutrition to most of the rice-eating Asian populations. Application of zinc solubilizing bacteria (ZSB) could be a sustainable agronomic approach to increase the soil available Zn which can mitigate the yield loss and consequently the nutritional quality of rice. Understanding the molecular interactions between rice and unexplored ZSB is useful for overcoming Zn deficiency problems. In the present study, the role of zinc solubilizing bacterial strain Enterobacter cloacae strain ZSB14 on regulation of Zn-regulated transporters and iron (Fe)-regulated transporter-like protein (ZIP) genes in rice under iron sufficient and deficient conditions was assessed by quantitative real-time reverse transcription PCR. The expression patterns of OsZIP1, OsZIP4, and OsZIP5 in root and shoot of rice were altered due to the Zn availability as dictated by Zn sources and ZSB inoculation. Fe sufficiency significantly reduced the root and shoot OsZIP1 expression, but not the OsZIP4 and OsZIP5 levels. Zinc oxide in the growth medium up-regulated all the assessed ZIP genes in root and shoot of rice seedlings. When ZSB was inoculated to rice seedlings grown with insoluble zinc oxide in the growth medium, the expression of root and shoot OsZIP1, OsZIP4, and OsZIP5 was reduced. In the absence of zinc oxide, ZSB inoculation up-regulated OsZIP1 and OsZIP5 expressions. Zinc nutrition provided to the rice seedling through ZSB-bound zinc oxide solubilization was comparable to the soluble zinc sulfate application which was evident through the ZIP genes’ expression and the Zn accumulation in root and shoot of rice seedlings. These results demonstrate that ZSB could play a crucial role in zinc fertilization and fortification of rice.